English-Speaking Adults' Labeling of Child- and Adult-Directed Speech Across Languages and Its Relationship to Perception of Affect - Soderstrom, Melanie; Casillas, Marisa; Gornik, Megan; Bouchard, Alexis; MacEwan, Sarah; Shokrkon, Anahita; Bunce, John (Frontiers in Psychology, 2021)
Child-directed speech, as a specialized form of speech directed toward young children, has been found across numerous languages around the world and has been suggested as a universal feature of human experience. However, variation in its implementation and the extent to which it is culturally supported has called its universality into question. Child-directed speech has also been posited to be associated with expression of positive affect or “happy talk”. Here, we examined Canadian English-speaking adults’ ability to discriminate child-directed from adult-directed speech samples from two dissimilar language/cultural communities; an urban Farsi-speaking population, and a rural, horticulturalist Tseltal Mayan speaking community. We also examined the relationship between participants’ addressee classification and ratings of positive affect. Naive raters could successfully classify CDS in Farsi, but only trained raters were successful with the Tseltal Mayan sample. Associations with some affective ratings were found for the Farsi samples, but not reliably for happy speech. These findings point to a complex relationship between perception of affect and CDS, and context-specific effects on the ability to classify CDS across languages.